Analysis of the impact of a flexible photovoltaic tile shape on its performance - Kurz, Dariusz; Morawska, Lena; Piechota, Robert; Trzmiel, Grzegorz (E3S web of conferences, 2018)
This paper addresses the subject of the building integrated photovoltaics (BIPV). The flexible thin-film CIGS module has been subjected to testing in order to investigate its electrical parameters and the possibilities of adaptation to the building structure. During analysis of performance of the tested building in real conditions, particular attention has been paid to changes in its parameters depending on the inclination angle and the shape of its surface in relation to the incident solar radiation. Current-voltage characteristics and power curves in the selected configuration of module deflections have been analysed. Changing the module’s inclination angle from the optimal 40° to 0° (horizontal arrangement of the module on the ground) reduced the value of generated current (by approx. 26%), voltage increase (by approx. 4%) and output power reduction by approx. 25%. The module generated a lower power compared to the basic test due to the irradiation limit reaching its surface (decrease in the irradiance value of less than 60% from 800 to 330 W/m 2 ). Bending the module at an angle 90° to the ground affected the large unevenness of solar radiation values reaching its surface and even greater losses of generated energy. The values of idle voltage, short-circuit current and voltage in MPP did not change much in relation to the base measurement, however, a large drop in the value of current in MPP was noted, which led to a significant reduction of output power. Thus, the need to strive for the most advantageous exposure of BIPV elements in relation to the sun was demonstrated and the losses on energy yields resulting from the integration of photovoltaic tiles into the body of the building have been estimated.